Perception About the Nodding Disease Syndrome and the Patient's Wellbeing - Immaculate Oyella (Uganda Christian University, 2024)
Nodding Disease (ND) is a disorder occurring in onchocerciasis endemic regions. The first nodding seizures occur in previously healthy children between the ages of 13-18 years (Echodu et al 2018). More than one child may be affected in a household, leading to a high burden of care, which in turn overwhelms the communities. The study employed mixed method, where both qualitative and quantitative design was used. Information or data collection was done using the questionnaire and interview guide within a short period. According to the study carried out based on the different objectives like to examine the perception people have about the nodding disease syndrome, to establish the relationship between people’s perception and the patients course of treatment and to find out what can be done to improve the wellbeing of the patients with nodding disease syndrome. These objectives helped in coming up with questions and interview guide which answered perception about nodding disease and the patients wellbeing. Most of the community members have negative perception about nodding disease, some view it has a disease which has not cure and it kills till death. This makes the community members develop fear on leaving with the patients and thus others are neglected and other patients do not receive treatment because they fear what community members will say about them. Some caregivers tie their children on ropes and trees because they think it’s the only way of helping them not fall on fire or water as caused by the seizure. The negative perception that community members have towards nodding disease syndrome, affects how the patients will receive care and treatment thus this leads to poor standards of living. The study has the following recommendations. Nodding disease syndrome still remains a big challenge in Kitgum district. The study has come up with the following recommendation. Sensitization should be done at all levels by the government and other NGOs. The people in Cities, Towns, Parishes, Sub-counties and villages need to be aware about nodding disease syndrome because the illness is affecting many people in Kitgum. Caregivers/parents should provide the necessary basic needs because the patients are their children and they should persevere until death do them apart.
Undergraduate dissertation